Adapting to Climate-Change-Induced Drought Stress to Improve Water Management in Southeast Vietnam - Thanh, Phong Nguyen; Le Van, Thinh; Minh, Tuan Tran; Ngoc, Tuyen Huynh; Lohpaisankrit, Worapong; Pham, Quoc Bao; Gagnon, Alexandre S.; Deb, Proloy; Pham, Nhat Truong; Anh, Duong Tran; Dinh, Vuong Nguyen (MDPI, 2023)
In Southeast Vietnam, droughts have become more frequent, causing significant damage and impacting the region’s socio-economic development. Water shortages frequently affect the industrial and agricultural sectors in the area. This study aims to calculate the water balance and the resilience of existing water resource allocations in the La Nga-Luy River basin based on two scenarios: (1) business-as-usual and (2) following a sustainable development approach. The MIKE NAM and MIKE HYDRO BASIN models were used for rainfall–runoff (R-R) and water balance modeling, respectively, and the Keetch–Byram Drought Index (KBDI) was used to estimate the magnitude of the droughts. The results identified areas within the Nga-Luy River basin where abnormally dry and moderate drought conditions are common, as well as subbasins, i.e., in the southeast and northeast, where severe and extreme droughts often prevail. It was also shown that the water demand for the irrigation of the winter–spring and summer–autumn crop life cycles could be fully met under abnormally dry conditions. This possibility decreases to 85–100% during moderate droughts, however. In contrast, 65% and 45–50% of the water demand for irrigation is met for the winter–spring and summer–autumn crop life cycles, respectively, during severe and extreme droughts. Furthermore, this study demonstrates that the water demand for irrigation could still be met 100% and 75–80% of the time during moderate, and extreme or severe droughts, respectively, through increased water use efficiency. This study could help managers to rationally regulate water in order to meet the agricultural sector’s needs in the region and reduce the damage and costs caused by droughts.